KAJIAN PENGELOLAAN BISNIS USAHATANI TERPADU DI JALAN BOULEVARD TONDANO - Maryo Lussy Grace Sumangkut; Jolanda Kitsia Juliana Kalangi; Wenny Tilaar (Sam Ratulangi University, 2020)
This study aims to determine the integrated farming business management on Tondano Boulevard Road, which involves 1) the ability to increase household income; 2) ability to reduce the risk of crop failure; 3) the ability to provide additional employment for families; 4) the ability to improve the efficiency of resource use; 5) ability to provide food for families; 6) ability to increase land productivity; and 7) the ability to improve the welfare of farm households. This research was carried out in November 2019 to February 2020 in the Tondano Boulevard Farming Business Area in Koya Village, South Tondano Sib-district. This study used qualitative research methods. Data collected through interviews, direct observations, document studies, and literature studies. Interviews and observations were made on informants namely farmers and village government as many as 10 people who were chosen purposively. Document studies include Minahasa in Figures 2018 and literature studies including journal articles. This research used qualitative data analysis. The results showed that the Integrated Farming Business Management on Tondano Boulevard Road was quite optimal including 1) able to increase the income of farmer households, namely farmers doing farming by planting rice, some were raising livestock and there were farmers who used part of their land to open a restaurant business, or rent out part of his farm to become a restaurant. 2) able to reduce the risk of crop failure through various businesses such as raising livestock, using part of the land for a place of business and renting part of the land as a place of business so that it can reduce the risk if there is no income due to crop failure. 3) able to provide additional employment for farming families, namely farmers who own agricultural land on Tondano Boulevard Road, in addition to being farmers who take care of their fields, they also have additional businesses such as raising livestock and use some of their land as a place of business such as restaurants. The existence of a side business has created job opportunities. 4) able to improve the efficient use of resources, namely farmers who utilize all available resources, energy, machinery and water that make rice planted will produce higher quality of rice. 5) enables farmers to provide food for their families, namely farmers who have agricultural land on Tondano Boulevard Road, most of them have enough income to provide food for their families. 6) able to increase land productivity that is able to manage their farming so that land productivity and farmers' income will increase. 7) able to improve the welfare of farmers' households. that is, farmers are able to meet their clothing needs, are able to obtain adequate housing, are able to access health services, and are able to gain access to education.*eprm*